Penerapan Model Pembelajaran Interaktif Berbasis Konsep Untuk Meningkatkan Hasil Belajar Kognitif Fisika Siswa - Susilawati Susilawati; Susi Putri Nawansi; Sutrio Sutrio; Aris Doyan (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2020)
The results of learning physics class X.C students at SMAN 1 Kediri are still low. One of the learning models that can increase the learning outcomes of students of class X.C physics is the Concept-Based Interactive Learning Model. This study aims to improve the results of learning physics class X.C students at SMAN 1 Kediri in the academic year 2015/2016 on Dynamic Electricity learning through the application of Concept-Based Interactive Learning Model. The type of research used is Classroom Action Research which is carried out in two cycles. Each cycle includes the stages of planning, implementing, observing and evaluating, and reflecting. The results showed that the mean value of students which is the result of learning in this study, the results in cycle I and cycle II are 72.95 and 79.10 respectively, with classical completeness sequences of 63.63 and 86.36%. Looking at the overall results of the study, it can be concluded that the application of the Concept-Based Interactive Learning Model can increase the learning outcomes of students of class X.C physics at SMAN 1 Kediri in the academic year 2015/2016 on the subject of Dynamic Electricity.